Exploration of Novel Hepatitis B Virus Capsid Assembly Modulators by Integrated Molecular Simulations. Issue 44 (25th November 2021) - Wang, Chenchen; Zhai, Na; Zhao, Yilan; Wu, Fengshou; Luo, Xiaogang; Ju, Xiulian; Liu, Genyan; Liu, Hui
Abstract: Capsid protein (Cp) plays an important role in the entire life cycle of Hepatitis B Virus (HBV) and is considered as a novel anti‐HBV target. A series of novel sulfamoylbenzamide (SBA) derivatives have been recently identified as HBV capsid assembly modulators (CAMs) with EC50 values at a low micromolar range. In this study, ligand‐ and receptor‐based molecular simulations were performed to understand the structure‐activity relationships (SARs) and the interaction mechanisms of these novel HBV CAMs. The constructed three‐dimensional quantitative SAR (3D‐QSAR) models exhibited good predictive abilities and well explained the SARs of these novel CAMs. Docking results suggested that HBV Cp TRP102 and THR128 might be key residues, which could form significant hydrogen bonds with these CAMs. Molecular dynamics (MD) results indicated that the most potent CAM could stably bind to the HBV Cp dimer or hexamer rather than the monomer, indicating that the inter‐dimer interface might be important for SBA CAMs to stably bind with HBV Cp. Furthermore, five novel hit compounds (N1 ‐5 ) as HBV CAMs were screened out by a comprehensive virtual screening. Compounds N1 and N2 were proved to bind well with the HBV Cp dimer and hexamer by MD simulations, and might have stronger interactions with the protein than the most potent SBA. These results might provide advantageous enlightenments for designing and developing novel HBV CAMs. Abstract : Hepatitis B virus (HBV) capsid protein (Cp) is considered as a novel anti‐HBV target. In this study, five novel hit compounds as HBV capsid assembly modulators were virtually screened out by the combination of ligand‐ and receptor‐based molecular simulations, including 3D‐QSAR and pharmacophore models, molecular dockings, molecular dynamics, and ADME predictions. The screened hits N1 and N2 were proved to be potential inhibitors of HBV Cp.